Studi Analisis Perbandingan Rugi Daya Pada Titik Sambung Pierching Connector Dengan Line Tap Connector Pada Jaringan Tegangan Rendah - Ahmad Syaifuddin F; Arief Budi Laksono; Suharijanto Suharijanto (Universitas Islam Lamongan, 2018)
Distribution system is divided into primary and secondary distribution networks. The primary distribution network is the network of the substation to the distribution, while the secondary distribution is the channel network from the substation transformer is distributed to the consumer or the load. Primary distribution network is better known as medium voltage network (JTM 20kV) while secondary distribution is low voltage network (JTR 220 / 380V). The distribution network is part of the power system closest to the customer or the load compared to the transmission network.At this time PT. PLN (Persero) experiencing power loss that occurs at the point of connection of low voltage on the use of pierching connector. This study is to analyze the calculation of loss of power at low voltage network (JTR) by doing comparison of measurement between input with output at connection point of pierching connector with line tap connector. For conditions required evaluation and analysis for replanning that takes into account the planning criteria such as voltage drop and take into account the loss of power.